Multi-decadal evolution of Crary Ice Rise region, West Antarctica, amid modern ice-stream deceleration - Hannah Verboncoeur; Matthew Ross Siegfried; Nicholas Holschuh; Jeremy Paul Winberry; Duncan Byrne; Wilson Sauthoff; Tyler Clark Sutterley; Brooke Medley (Journal of Glaciology, 2025)
The ongoing deceleration of Whillans Ice Stream, West Antarctica, provides an opportunity to investigate the co-evolution of ice-shelf pinning points and ice-stream flux variability. Here, we construct and analyze a 20-year multi-mission satellite altimetry record of dynamic ice surface-elevation change (dh/dt) in the grounded region encompassing lower Whillans Ice Stream and Crary Ice Rise, a major pinning point of Ross Ice Shelf. We developed a new method for generating multi-mission time series that reduces spatial bias and implemented this method with altimetry data from the Ice, Cloud, and land Elevation Satellite (ICESat; 2003–09), CryoSat-2 (2010–present), and ICESat-2 (2018–present) altimetry missions. We then used the dh/dt time series to identify persistent patterns of surface-elevation change and evaluate regional mass balance. Our results suggest a persistent anomalous reduction in ice thickness and effective backstress in the peninsula connecting Whillans Ice Plain to Crary Ice Rise. The multi-decadal observational record of pinning-point mass redistribution and grounding zone retreat presented in this study highlights the on-going reorganization of the southern Ross Ice Shelf embayment buttressing regime in response to ice-stream deceleration.